Regulating Convergence: Challenges for Contemporary Media in Indonesia - Hellena Yoranita Souisa (Department of Communications, Universitas Islam Indonesia, 2017)
This paper examines the implications of media liberalization and media convergence to regulatory issues and journalism practices in Indonesia. While technologies are being used to serve the economic interests of media companies, corporate concentration and technological convergence effectively disempower media workers. It will do so through an in-depth analysis of the current trends and case studies in the Indonesian media industry. The Indonesian case shows how media liberalization affects Indonesian media landscape at a first place, and how the media landscape is then shaped by conglomeration and convergence. Using the concept of diversity, media scholars are still debating the consequences of liberalization and convergence, to see whether those will undermine journalism and threaten the diversity of voices as the heart of media in democracy. This creates another challenge for regulatory bodies in Indonesia. On one hand, a free and competitive economic marketplace, a consideration of competitive markets is critical. On the other hand, there should be some tools to ensure media pluralism and diversity (ownership and content), hence provide necessary protections for the public. May there are interventions needed from the government body regarding this double-edge sword situation, a clear distinction needs to be drawn between regulation in the public interest and regulation to protect against market failure.Keywords: Indonesia; media ownership, media concentration, convergence, content diversity, political economy, policy